Effects of density of anisotropic microstamped silica thin films on guided bone tissue regeneration - In vitro study (2013)
The growing demand for better implant aesthetics has led to increased research on the development of all-ceramic dental implants. The use of microtextured coatings with enhanced properties has been presented as a viable way to improve tissue integrability of all-ceramic implants. The aim of this study was to evaluate the effects of different densities of anisotropic microtextured silica thin films, which served as a model coating, on the behavior of human osteoblast-like cells. The differential responses of human osteoblast-like cells to anisotropic silica microtextures with varying densities, produced via a combination of sol-gel and soft lithography processing, were evaluated in terms of alignment, elongation (using fluorescence microscopy), overall cellular activity, and the expression/activity levels of alkaline phosphatase (ALP). Statistical analysis was conducted using one-way ANOVA/Tukey HSD post hoc test. The thin films were thoroughly characterized via scanning electron microscopy/energy dispersive spectroscopy, Fourier transform infrared, and contact angle measurements. Thin film characterization revealed increased nanoscale roughness and reduced wettability on the micropatterned surfaces. Cell culture experiments indicated that the microtextures induced cell alignment, elongation, and guided colonization on the surface. Cells cultured on denser micropatterns exhibited increased metabolic activity (t = 14-21 days). The early expression/activity levels of ALP released into the medium were found to be significantly higher only on the least dense micropattern. These results suggest the possibility that microstructured silica thin films could be used to guide and enhance peri-implant cell/tissue responses, potentially improving tissue integration for metallic and all-ceramic dental implants. © 2013 Wiley Periodicals, Inc.